IL-2 Signaling Axis Defects: How Many Faces? - Consonni, Filippo; Favre, Claudio; Gambineri, Eleonora (Frontiers in Pediatrics, 2021)
CD25, Signal transducer and activator of transcription 5B (STAT5B) and Forkhead box P3 (FOXP3) are critical mediators of Interleukin-2 (IL-2) signaling pathway in regulatory T cells (Tregs). CD25 (i.e., IL-2 Receptor α) binds with high affinity to IL-2, activating STAT5B-mediated signaling that eventually results in transcription of FOXP3, a master regulator of Treg function. Consequently, loss-of-function mutations in these proteins give rise to Treg disorders (i.e., Tregopathies) that clinically result in multiorgan autoimmunity. Immunodysregulation, Polyendocrinopathy Enteropathy X-linked (IPEX), due to mutations in FOXP3, has historically been the prototype of Tregopathies. This review describes current knowledge about defects in CD25, STAT5B and FOXP3, highlighting that these disorders both share a common biological background and display comparable clinical features. However, specific phenotypes are associated with each of these syndromes, while certain laboratory findings could be helpful tools for clinicians, in order to achieve a prompt genetic diagnosis. Current treatment strategies will be outlined, keeping an eye on gene editing, an interesting therapeutic perspective that could definitely change the natural history of these disorders.